2019
DOI: 10.14715/cmb/2019.65.5.11
|View full text |Cite
|
Sign up to set email alerts
|

Effect of urea, compost, manure and bio-fertilizers on yield, percentage and composition of fatty acids of sesame seed oil (Sesamum indicum L.)

Abstract: This study was carried out in Iran during two growing seasons 2016-2017. Sesame is one of the earliest oilseed plants, high oil percentage and high content of unsaturated fatty acids, especially oleic acid and linoleic acid, have led to an increase in the nutritional quality of sesame oil. Accordingly, a two-year experiment was conducted as factorial based on randomized complete block design with three replications. The evaluated factors included four levels of urea as nitrogen fertilizer (0, 33, 66 and 100% o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0
2

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 18 publications
1
2
0
2
Order By: Relevance
“…In particular, the maximum two-year average values of the oil content in palmitic, pentadecanoic, and behenic acid were 3.62%, 0.42%, and 0.52% w/w, respectively. As for palmitic acid, these findings are comparable to those of Ganjineh et al (2019), who discovered that using compost in sesame production resulted in a higher amount of palmitic acid in the seed oil as compared to the applications of urea and manure. For stearic and arachidic acid, the maximum two-year means were recorded in the untreated (control) with the values being 2.05% and 0.97% w/w, respectively.…”
Section: Discussion Discussion Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…In particular, the maximum two-year average values of the oil content in palmitic, pentadecanoic, and behenic acid were 3.62%, 0.42%, and 0.52% w/w, respectively. As for palmitic acid, these findings are comparable to those of Ganjineh et al (2019), who discovered that using compost in sesame production resulted in a higher amount of palmitic acid in the seed oil as compared to the applications of urea and manure. For stearic and arachidic acid, the maximum two-year means were recorded in the untreated (control) with the values being 2.05% and 0.97% w/w, respectively.…”
Section: Discussion Discussion Discussionsupporting
confidence: 82%
“…In the current research, oleic acid was the second higher MUFA in content and its highest content was observed after the application of urea with and without nitrification and urease inhibitors with the two-year average values amounting to 20.23% and 19.08% w/w, respectively. The positive effect of increasing levels of inorganic N fertilization on oleic acid and its content has also been observed in other crops, such as sesame (Ganjineh et al, 2019), sunflower (Alzamel et al, 2022) and cotton (Sawan, 2018).…”
Section: Discussion Discussion Discussionmentioning
confidence: 68%
“…Organic fertilizers have been proved for their ability to promote sesame's growth parameters including chlorophyll content, plant heights, number of seeds per capsule, number of capsules per plant, and 1,000-seed weights and seed yields [12,13]. For instance, the application of organic fertilizers and biofertilizers was able to improve the sesame yield, soil fertility, and seed oil quality with higher contents of oleic, stearic, and palmitic acids, but lower contents of linolenic and linoleic acids [14]. Interestingly, the use of plant growth promoting rhizobacteria (PGPR) processing nitrogen (N) fxing ability and phosphorous (P) solubilization as a biofertilizer could reduce the chemical fertilizer input for sesame [15][16][17] and enhance its N and P uptake [18,19].…”
Section: Introductionmentioning
confidence: 99%
“…Συγκεκριµένα, οι µέγιστες µέσες τιµές τριετίας της περιεκτικότητας του ελαίου σε µυριστικό και παλµιτικό οξύ ήταν 0,50% και 15,65% w/w, αντίστοιχα. Τα εν λόγω αποτελέσµατα είναι παρόµοια µε τα αποτελέσµατα των Ganjineh et al (2019), όπου διαπίστωσαν ότι η εφαρµογή κοµπόστ σε καλλιέργεια σουσαµιού είχε ως αποτέλεσµα τη µεγαλύτερη περιεκτικότητα σε µυριστικό και παλµιτικό οξύ στο έλαιο σε σχέση µε την εφαρµογή ουρίας και κοπριάς. Για το στεατικό οξύ, η µέγιστη µέση τιµή τριετίας εντοπίστηκε στον µάρτυρα και ήταν ίση µε 1,99% w/w.…”
unclassified
“…Όσον αφορά το ελαϊκό οξύ, η µεγαλύτερη περιεκτικότητα βρέθηκε µετά την εφαρµογή της κοπριάς µε τη µέση τιµή τριετίας να ανέρχεται σε 26,27% w/w. Η θετική επίδραση της κοπριάς έναντι της ανόργανης λίπανσης στο ελαϊκό οξύ και την περιεκτικότητα του έχει επίσης παρατηρηθεί και σε άλλες καλλιέργειες, όπως η ελαιοκράµβη (Gao et al, 2010) και το σουσάµι (Ganjineh et al, 2019). Το λινελαϊκό οξύ παρουσίασε τις µεγαλύτερες περιεκτικότητες στον µάρτυρα και το κοµπόστ µε µέσες τιµές τριετίας 59,71% και 59,19% w/w, αντίστοιχα.…”
unclassified